PENGARUH PENGELUARAN KESEHATAN DAN PENDIDIKAN SERTA INFRASTRUKTUR TERHADAP INDEKS PEMBANGUNAN MANUSIA DI PROVINSI MALUKU - Abdul Kadir Mahulauw; Dwi Budi Santosa; Putu Mahardika (Jurnal Ekonomi Pembangunan, 2016)
The purpose of research is to see how the effect of government spending on education, health, and infrastructure to increase HDI District / City in Maluku Province. The research method using path analysis (path analysis) with the test criteria at the level of 5% error to view the Maluku provincial government spending on education, health, infrastructure, and also the income per capita as an intervening variable. Results of the analysis showed that the simultaneous three types of government spending such a significant effect on the HDI. It was found that with R Square of 68.1% and 31.9% explained by other variables outside the model and the partial income per capita as an intervening variable no significant effect on the increase in the HDI.